Grassland Management Employment Opportunities in Kogi State, Nigeria - Nwakile, Toochukwu C.; Okadi, Ashagwu O.; Ojiako, Chiamaka C.; Ekenta, Lilian U. (Journal of Home Economics Research, 2024)
The study focused on grassland management employment opportunities in Kogi State, Nigeria. Specifically, it determined employment opportunities in grassland management, challenges that could hinder employment in various grassland management opportunities, and ways of ameliorating the challenges that could hinder employment in various grassland management opportunities the state. Survey research design was used. Population was made up of 81 respondents consisting of 42 Agricultural Extension lecturers and 39 Extension agents. Questionnaire was utilized for data collection. It was validated by three experts. Cronbach Alpha reliability coefficient of 0.82 was obtained for the instrument. Data were analyzed using mean and standard deviation and t-test. Finding include 12 employment opportunities available in grassland management such as Grassland Manager ( = 3.32) and Grazing assistant ( = 3.62). Also 10 challenges that could hinder employment opportunities in various grassland management opportunities were identified such as climate-related challenges such as droughts ( = 3.72) and low reputation of various grassland management opportunities ( = 3.72) 13 ways of ameliorating challenges that could hinder employment opportunities were identified. These include building synergies with NGOs that already provide skills for grassland management ( = 3.46) and improving access to resources and infrastructure needed in grassland management ( = 3.24). Further, there was no significant differences between the mean responses of Agricultural Extension lecturers and Extension Agents on employment opportunities available in grassland management, challenges that could hinder employment opportunities and ways of ameliorating the challenges, all at 0.05 level of significance.